Study of energy dissipation and absorption in submicrocrystalline titanium under quasi-static and dynamic loading - Plekhov, Oleg Anatolievich; Chudinov, Vasiliy Valerievich; Leontev, Vladimir Arkadievich; Najmark, Oleg Borisovich (Computational Continuum Mechanics, 2008)
This work is devoted to experimental investigation of mechanical and thermodynamic properties of submicrocrystalline titanium under quasi-static tension and dynamic compression. Submicrocrystalline titanium specimens with grain size of 300 nm were obtained from the bars produced by equal channel angular pressing. The temperature kinetics during plastic deformation was measured using an infrared camera CEDIP Silver 450 (spectral range of 3-5 gm, temperature sensitivity of 0.025K). The grinding of titanium grains led to an increase in yield stress 260% and 25% under quasi-static and dynamic loading conditions, respectively. The study of thermodynamics of the process showed that the transition from elastic to plastic deformation in titanium was accompanied by intensive heat dissipation. The relative value of stored energy in submicrocrystalline titanium under quasi-static and dynamic loading was higher than that in coarse-grained titanium. The value of stored energy in submicrocrystalline titanium under dynamic compression remained almost constant and did not depend on the rate and amplitude of loading in the examined range of deformation rates.